Menologia of cyrillic early printed liturgical tetraevangelia issued in Vilnius - Ostapczuk, Jerzy (Knygotyra, 2023)
Merely four out of 110 Cyrillic early printed liturgical Tetraevangelia were printed in Vilnius. Three of them were issued at Mamonich Printing House (1575, 1600 and ca. 1620) and one at Vilnius Brotherhood of the Holy Spirit (1644). As these four editions were frequently consulted in various book studies and completely neglected in liturgical scholarship, the commemorations of saints and feasts present in Menologia (i.e., in the fixed liturgical calendar) of all of Vilnius Gospels and other typologically homogeneous books were chosen as the subject of this research. This study was based on all Cyrillic early printed liturgical Tetraevangelia, i.e., books issued before the year 1800. Special attention was paid to the three 16th c. Moscow (so-called anonymous) and the first two Lviv editions (issued in 1636 and 1644), as they are sometimes treated as the origins of Vilnius Gospels. Textual and liturgical analyses of Menologia were the main research methods applied in this publication. The varying number of days in the twelve months, the presence or absence of saints and feasts, as well as the verbatim correspondence of the names of commemorations and the information on the recitation of the Gospel fragments at the Divine Liturgy have been analysed. The outcomes of the undertaken research have proven that three Mamonich Gospel editions copied the Muscovite liturgical tradition, whereas Vilnius Brotherhood’s Tetraevangelion fully reproduced the first Lviv Gospel. This means that one of the three 16th c. Moscow anonymous Tetraevangelia had served as the origin for the first Mamonich edition, and that the fourth Vilnius Gospel is an accurate copy of the first Lviv Tetraevangelion. Textual variants revealed in Vilnius Gospel editions must be treated as the result of the printers’ text revision. A full list of all 203 commemorations present in the Menologia of the four Vilnius Tetraevanalia was added to this study.